PET packing return: scenarios considering the liability of manufacturers and dealers - Lima, Diego Damasio de; Souza , Marcos Leandro Hoffmann; Eidelwein, Fabrício; Sellitto, Miguel Afonso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The disposal of PET packaging in landfills, combined with reduced rates of reuse and recycling of the material result in governamental movements in search of more suitable solutions to the environment. The responsibility of manufacturers for packaging of their products is a trend that consolidates every day. In the beverage industry, the reverse logistics of packaging can become reality in the coming years. Laws are being dealt to blame the manufacturers for collecting the packaging, as occurs in the crop protection industry. Concerning the presented context, this study aims to understand what would be the impact of a government decision of this nature, as well as factors, constraints and bottlenecks to effective implementation of policies of reverse logistics of PET. Thus, the working method used initiated by a literature search, which served as the basis for assessments of future context, following the technique of scenario planning. Among the main findings, it was found that many companies will have immense trouble following this market from this new law.